2005
DOI: 10.1162/0898929053747603
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potential Correlates of Long-Term Memory for Briefly Presented Faces

Abstract: Abstract& Electrophysiological studies have investigated the nature of face recognition in a variety of paradigms; some have contrasted famous and novel faces in explicit memory paradigms, others have repeated faces to examine implicit memory/ priming. If the general finding that implicit memory can last for up to several months also holds for novel faces, a reliable measure of it could have practical application for eyewitness testimony, given that explicit measures of eyewitness memory have at times proven f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
4
15
2
Order By: Relevance
“…For example, short-term priming of location or stimulus features has been found for covert attention (Maljkovic & Nakayama, 1994. Furthermore, our findings extend previous knowledge on perceptual-priming tasks, in which learning is known to occur independently of awareness (Joyce & Kutas, 2005;Meister et al, 2005;Wiggs & Martin, 1994.…”
Section: Discussionsupporting
confidence: 87%
“…For example, short-term priming of location or stimulus features has been found for covert attention (Maljkovic & Nakayama, 1994. Furthermore, our findings extend previous knowledge on perceptual-priming tasks, in which learning is known to occur independently of awareness (Joyce & Kutas, 2005;Meister et al, 2005;Wiggs & Martin, 1994.…”
Section: Discussionsupporting
confidence: 87%
“…Akin to the face recognition units of the face recognition model Burton et al, 1990;Bruce & Young, 1986), the N170 may be the premier stage in which face processing depends on familiarity. Although this is earlier than previously reported (e.g., Joyce & Kutas, 2005), our data suggest that the perceptual stage of face processing as reflected by the N170 depends on the existence of person-specific semantic information associated with the particular face.…”
Section: Discussioncontrasting
confidence: 81%
“…Here, however, no differences were found for the LPC between famous and unknown eyes. A few studies have shown that the LPC is more positive to familiar than unfamiliar whole faces (Curran and Hancock 2007;Joyce and Kutas 2005;Yovel and Paller 2004), even when individuals are not aware that they had seen faces before (Schweinberger 1995;Seeck et al 1997). Nevertheless, our results are consistent with those of Jemel et al (2005) who observed no significant difference from 400 to 600 ms between unfamiliar and famous faces that were previously primed with the same-person.…”
Section: Discussionsupporting
confidence: 82%
“…This may at the same time explain why the effects were found for both unknown and famous eyes. Previous studies that reported decreased N170 amplitudes after face-repetition (Henson et al 2002;Heisz et al 2006;Itier and Taylor 2004) and/or increased LPC amplitudes (Bentin and Deouell 2000;Eimer 2000;Schweinberger 1995;Schweinberger et al 2002;Henson et al 2003;Joyce and Kutas 2005) commonly used high quality images of whole faces in which identification was relatively easy. Future studies should investigate whether there is an effect Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation